Milking the Data : Measuring Income from Milk Production in Extensive Livestock Systems -- Experimental Evidence from Niger - Zezza, Alberto; Federighi, Giovanni; Adamou, Kalilou; Hiernaux, Pierre (World Bank Group, Washington, DC, 2014)
Milk is an important source of cash and nutrients for many households in developing countries. Yet, the understanding of the role of dairy production in livelihoods and nutritional outcomes is hindered by the lack of decent quality household survey data. Data on milk off-take for human consumption are difficult to collect in household surveys for several reasons that make accurate recall challenging for the respondent (continuous production and seasonality, among others). As a result, the quantification and valuation of milk off-take is particularly difficult in household surveys, introducing possibly severe biases in the computation of full household incomes and farm sales, as well as in the estimation of the contribution of livestock (specifically dairy) production in agricultural value added and the livelihoods of rural households. This paper presents results from a validation exercise implemented in Niger, where alternative survey instruments based on recall methods were administered to randomly selected households and compared with a 12-month system of physical monitoring and recording of milk production. The results of the exercise show that reasonably accurate estimates via recall methods are possible and provide a clear ranking of questionnaire design options that can inform future survey operations.